Analisa Perbandingan Algoritma Unary Code Dan Algoritma Prefix Code Untuk Kompresi File PDF - Radiah, Apni Radiah (Jurnal Sains dan Teknologi Informasi, 2024)
A pdf file (Portable Document Format) is a type of document or file format for digital document exchange purposes. Problems with pdf files often occur when we send files with a large capacity so that the process of sending files is wasteful and it will take a long time in the process of sending pdf files. In overcoming this problem, you have to do a compression technique first so that the pdf file saves on sending files. After carrying out the compression process, you will get a smaller file than before. And the goal is to save storage space and also speed up the shipping process.In the compression process, the Prefix Code Algorithm has better compression results than the Unary Code Algorithm, namely the Prefix Code Algorithm obtains a total value of 5.420% while the Unary Code Algorithm obtains a total value of 5.220% in compressing Pdf files. The Prefix Code algorithm obtains greater results compared to the Unary Code algorithm. So the conclusion is that the Prefix Algorithm is better than the Unary Code Algorithm for compressing Pdf files.